Improving Parental Knowledge of Adolescent Sexual and Reproductive Health Through Audio-Visual Education in a Special Needs School Setting - Harianja, Ristina Rosauli; Arinda, Yosi Duwita; Nurdin, Muhammad Akbar; Dewi, Citra Kumala (RRZ Scientific Publishing, 2025)
Adolescents with Special Needs often face barriers to sexual and reproductive health (SRH) information, and parents are key sources of guidance. This study evaluated the effect of audio-visual SRH education on parental knowledge in a special needs school setting. A pre-experimental one-group pretest-posttest study was conducted at a Sekolah Luar Biasa (SLB) or special needs school in rural area Indonesia (January-July 2023). Fifty parents were recruited by purposive sampling from a population of 96. Knowledge was measured using a structured questionnaire before and after an audio-visual education session. Differences in scores were tested using the Wilcoxon signed-rank test (alpha= 0.05). Most parents (68.0%) had previously received SRH information. Mean knowledge increased from 13.38 ± 3.016 at pretest to 19.52 ± 2.53 at posttest. The Wilcoxon signed-rank test showed a significant improvement (Z = -6.10, p < 0.001), with 49 participants improving and one unchanged (effect size r=0.86). Audio-visual education was associated with a significant improvement in parental SRH knowledge. Integrating multimedia-based education into school-parent collaboration may strengthen SRH support for adolescents with special needs.